Pemanfaatan Teknologi dalam Meningkatkan Kualitas Pendidikan di SMA Swasta Teladan Medan - Jeta Amina Siahaan; Fauzi Kurniawan; Rachel Nadia S B Banjarnahor; Sentia Br Malau; Tamasya Mercy Raja Guk Guk; Esabella Sinaga (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Technology has become an essential need for various groups in everyday life, including in the world of education. Technology such as television and mobile phones play an important role in supporting students to develop technological skills. This research focuses on developing an educational information system at Teladan Medan Private High School which aims to manage student, teacher and learning data effectively. This information system is expected to be able to improve the management and use of technology in the teaching and learning process. The research method used is field research with a qualitative approach. This approach views the research object as an interrelated system and functions to describe the phenomena that exist at the research location, namely at SMAS Teladan Medan. The instruments used are adapted to field conditions, with the aim of obtaining reliable data. It is hoped that this research can contribute to the development of information technology in education, especially at the high school level.